НЕФЕЛИН-ПИРОКСЕН-ПИРРОТИНОВЫЕ И ПИРОКСЕН-ПИРРОТИНОВЫЕ ПОРОДЫ КИЯ-ШАЛТЫРСКОГО МАССИВА (КУЗНЕЦКИЙ АЛАТАУ) - Гринев О.М.; Родыгина В.Г. (My University, 1988)
The results of geological, petrographical and mineralogica] investigations arc discus sod for eoinpositionally original no|)!ielino-pyroxeiio-pyrrhotilo and pyroxeno-p\ rrhotile rocks nianil'estated in a series ol* dykes and dyke-like bodies. The local concentrations ol* py rrhotile are related to these rocks. Minoralogieal characteristic ol* pyrrlioliti and jointly manifestatod cobalt-bearing pentlandite. magnetite and other minerals are di.-cussed. The magmatic origin ol ore mineral bodies are established. Their origin is discusse<l on the basis of liquation Segregation ol" fluid saturated ultrabasic I'oidolitic magma.
Keywords: НЕФЕЛИНОВЫЕ РУДЫ; НЕФЕЛИН-ПИРОКСЕНОВЫЕ ПОРОДЫ